Cervical Rib Surgery: A Study of 20 Cases - Rahman, M Lutfor; Mohammod, G; Alam, I; Ali, MS (TAJ: Journal of Teachers Association, 2009)
Cervical ribs give rise to vascular and neurogenic manifestation in the upper limb due to stretching and friction of neurovascular bundle in the base of the neck by numerous mechanisms that includes cervical ribs, anomalous ligament & hypertrophy of the scalenus anticus muscle. Controversy surrounds the diagnosis and management of thoracic outlet syndrome with or without cervical ribs. This is a small study of 20 cases carried out from 1994 to 2003 at RMCH, and some private hospitals. Out of them, 15 patients (75%) were male and 5 patients (25%) were female. The age of the patients was between 15 to 48 years (mean age 33 years) Unilateral cervical ribs were present in 75% cases and the rest 25% had bilateral cervical ribs. Only 3 patients presented with gangrenous upper limb. One of the patient attended to orthopedic surgeon first and amputation was planned. All the patient were treated through supra clavicular approach by excision of cervical ribs together with fibrous band. Only one patient did not respond to this initial surgery as symptoms persist and re-operation done by excision of first-rib and ultimately that patient become symptom free. In this study, authors explained their own experience of various way of presentation of cervical ribs, aetiology, different modalities of the treatment and their out come. doi: 10.3329/taj.v17i1.3482 TAJ 2004; 17(1) : 10-12